Small Intestinal Ischemia with Pneumatosis in a Young Adult: What Could Be the Cause?. (5th February 2013) - Nidimusili, Amara Jyothi; Mennella, Jenna; Shaheen, Khaldoon
Abstract : This case highlights one of the infrequent complications of a commonly abused substance. A particular high index of suspicion of ischemic bowel is associated with cocaine abuse and should be included in the differential diagnosis of any young adult or middle-aged patient with abdominal pain and/or bloody diarrhea, particularly in the absence of other predisposing factors. To our knowledge, we report a rare case of ischemic small bowel associated with gangrene and pneumatosis intestinalis due to cocaine abuse.